Use of e-Counseling to Enhance Adherence of Patient Tuberculosis: A Systematic Review - Sulistiawati, Rani; Sukartini, Tintin; Makhfudli, Makhfudli; Mau Leon, Fransiska (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Electronic health, or e-Health, can revolutionize the clinical management of tuberculosis (TB) through enhanced treatment efficiency and effectiveness, among other benefits. Regarding TB, this may entail teleconsultation, which allows medical professionals to speak with TB specialists remotely, or telemonitoring, which allows patients to be remotely monitored using digital technology. This paper aims to determine the effectiveness of tele-counselling in enhancing adherence to patient tuberculosis. We used the Scopus database, Science Direct, Ebsco Host, and PubMed for English published between 2018 and 2023: the Joanna Briggs Institute guidelines assessed eligibility, PRISMA quality, and  a checklist to guide this review. The articles have case-control, quasi-experimental, mixed method studies, and randomized control trials (RCT). E-counseling was included in the analysis if they focused on tuberculosis and were excluded if unrelated to other disease areas. Fifteen articles that could be used in this review were found. The majority of the population were adults. Results of the review showed that most m-Health apps support tuberculosis treatment. There are numerous ways that electronic counseling, or “e-counseling,” may improve adherence to TB treatment. This study illustrated how m-health might improve patient comprehension and adherence. The five goals of the World Health Organization (WHO) e-Health framework are being met using more e-Health treatments to treat TB. Among the technology interventions demonstrated to have a significant, positive effect on disease outcomes are smartphone apps, mobile voice conversations, SMS, and instructive films.  Keywords: E-counselling; m-Health; tuberculosis; patient adherence